Autologous serum skin test as an indicator of chronic autoimmune urticaria in a tertiary care hospital in South India - Adaikalampillai Ganapathy Vikramkumar; Sheela Kuruvila; Satyaki Ganguly (Wolters Kluwer Medknow Publications, 2014)
Background: Autologous serum skin test (ASST) is a simple in-vivo clinical test for the detection of basophil histamine releasing activity and to diagnose chronic autoimmune urticaria (CAU) among chronic spontaneous urticaria (CSU) patients. Diagnosing these patients is also important as they may need high doses of antihistamines and systemic corticosteroids during acute exacerbations. Aims and Objectives: The aim of this study is to study the prevalence of CAU among cases of CSU by using ASST. Materials and Methods: This was a cross-sectional study done among 48 patients presenting with CSU. Detailed history, physical examination and routine investigations were recorded for all patients. ASST was done on all the 48 patients. Results: Of the 48 patients included in the study, 20 patients (41.6%) were ASST positive, while the remaining 28 (58%) were ASST negative. The median duration of disease in both ASST positive and negative patients was 1 year. ASST positivity was higher (66.6%) among patients with a history of round shaped weals, though not statistically significant. ASST positivity was seen in 5 (71.4%) out of seven patients with systemic involvement, which was again not statistically significant. Conclusion: Our study did not show any significant difference between patients with and without antibodies regarding mean age and sex distribution, clinical morphology of individual weals, duration, severity, systemic symptoms, angioedema, atopy, and association with other autoimmune conditions.